Influence of polarization engineering in InxAlyGaN1−x−y back-barrier on AlGaN coupled channel MOS-HEMT with HfO2 gate dielectric for millimeter wave application - K, Lakshmi Priya; S, Karthik (Frontiers in Materials, 2025)
This study investigates a high-performance double-tiered T-gate AlGaN coupled-channel MOS-HEMT that incorporates an InAlGaN back-barrier and employs HfO2 as the gate dielectric. The device performance is analysed using Sentaurus TCAD simulations, which include mobility models, hydrodynamic and thermodynamic effects, piezoelectric polarization, and impact ionization models. The epitaxial structure utilizes an AlGaN coupled-channel to enhance carrier confinement and a lattice-matched InAlGaN back-barrier to minimize buffer leakage. As a result, the device achieves a drain current of 1.19 A/mm, a peak transconductance of 400 mS/mm, a drain-induced barrier lowering (DIBL) of 72 mV/V, and a threshold voltage (Vth) shift of −2 V. The double-tiered T-gate with field-plate extensions significantly improves breakdown performance, achieving a blocking voltage of 640 V. Furthermore, experimental measurements demonstrate a cut-off frequency (fT) of 206 GHz with a gate length of 60 nm. The device exhibits a substantial improvement in current drive due to the use of a graded AlGaN coupled-channel combined with an InAlGaN back-barrier, compared to conventional AlGaN composite-channel HEMTs. Additionally, the proposed design demonstrates enhanced frequency performance, making it a promising solution for high-efficiency power switching and millimetre-wave applications.